A Severe Accident Caused by an Ocellate River Stingray (Potamotrygon motoro) in Central Brazil: How Well Do We Really Understand Stingray Venom Chemistry, Envenomation, and Therapeutics? - Nelson Jorge da Silva; Kalley Ricardo Clementino Ferreira; Raimundo Nonato Leite Pinto; Steven Douglas Aird (Toxins, 2015)
Freshwater stingrays cause many serious human injuries, but identification of the offending species is uncommon. The present case involved a large freshwater stingray, Potamotrygon motoro (Chondrichthyes: Potamotrygonidae), in the Araguaia River in Tocantins, Brazil. Appropriate first aid was administered within ~15 min, except that an ice pack was applied. Analgesics provided no pain relief, although hot compresses did. Ciprofloxacin therapy commenced after ~18 h and continued seven days. Then antibiotic was suspended; however, after two more days and additional tests, cephalosporin therapy was initiated, and proved successful. Pain worsened despite increasingly powerful analgesics, until debridement of the wound was performed after one month. The wound finally closed ~70 days after the accident, but the patient continued to have problems wearing shoes even eight months later. Chemistry and pharmacology of Potamotrygon venom and mucus, and clinical management of freshwater stingray envenomations are reviewed in light of the present case. Bacterial infections of stingray puncture wounds may account for more long-term morbidity than stingray venom. Simultaneous prophylactic use of multiple antibiotics is recommended for all but the most superficial stingray wounds. Distinguishing relative contributions of venom, mucus, and bacteria will require careful genomic and transcriptomic investigations of stingray tissues and contaminating bacteria.